Accounting Conservatism, Audit Quality, Gender Board of Directors: Earnings Management - Febriana Lestari , Puput; Hariyani, Diyah; Nur Sulistyowati, Liliek (Journal of Business and Management Review, 2024)
Research Aims: This study aims to determine the effect of accounting conservatism, audit quality, and board of directors gender on earnings management. The population in this study is companies included in the Kompas 100 Index for the 2020-2022 period Design/methodology/approach: The type of research used is descriptive research with a quantitative approach and uses data analysis methods in the form of multiple regression analysis processed with the SPSS 23 program. Sampling in this study used purposive sampling techniques with a total of 216 samples. The data collected in this study is secondary data taken from the annual report on Kompas 100 Index companies for the 2020-2022 period with a total of 72 companies Research Findings: Based on the results of tests that have been carried out show that accounting conservatism has a negative and significant effect on earnings management. Audit quality does not have a positive and significant effect on earnings management. The gender of the board of directors negatively and significantly affects earnings management. Theoretical Contribution/Originality: his study sheds new light on how gender diversity on boards influences the effectiveness of accounting conservatism and audit quality in controlling earnings management. By exploring these interactions, we offer fresh insights into how diverse perspectives can enhance financial integrity and improve corporate governance practices. Keywords: Accounting Conservatism; Audit Quality; Board of Directors Gender; Earnings Management